HIPEREALITAS DALAM WEBSITE MERCEDES-BENZ THE NEW A CLASS - Aditya Nirwana (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
This study of the Mercedes-Benz The New A Class website is a case study carried out with the aim of finding out that the Mercedes-Benz The New A-Class website has elements of hyper-signs as part of hyperreality, as well as proving that the Mercedes-Benz The New website A-Class is a simulation, with post-structural sign/semiotic analysis and with Jean Baudrillard's simulation theory and hyperreality approach. Some conclusions obtained from this study are; firstly, the two VRs on the Mercedes-Benz A Class website here are a simulation process, and secondly the virtual reality in it is a duplication of itself, because the reality reference does not exist. Second, on the Mercedes-Benz A Class website, pseudo/original, fake/imitation, past/present, natural/artificial are mixed up and overlapping, so that they can no longer be differentiated. This shows that the Mercedes-Benz A Class website is a form of hyperreality.